A Heavy Load: Challenges and Current Practices for Volunteer Managers in the USA, Australia, and Canada. Issue 1 (1st January 2020) - Kappelides, Pam; Johnson, Tobi
ABSTRACT: Volunteers make a significant contribution to the infrastructure of western societies, and volunteer managers or coordinators are the important conduit that ensures volunteers are managed and supported. This article addresses the key challenges faced by volunteer managers and coordinators in the USA, Australia, and Canada. The results were conducted in 2015–2018. A total of 5, 268 responses were gathered over the 4 years of the survey. This research study has provided evidence that volunteer managers have several challenges in their roles and require the support of their nonprofit organization to manage volunteers. Volunteer managers need to have resources, time and support from management to manage their volunteers and thereby contributing to the function of their organizations.